Stabilization and fluorescence light-up of G-quadruplex nucleic acids using indolyl-quinolinium based probes. Issue 10 (1st March 2022) - Biswas, Annyesha; Singh, Sushma B.; Todankar, Chaitra S.; Sudhakar, Sruthi; Pany, Sushree Prangya Priyadarshinee; Pradeepkumar, P. I.
Abstract : Small molecule based fluorescent probes for the stabilization and sensing of G-quadruplex DNAs. Abstract : G-Quadruplexes (G4s) are four-stranded motifs formed by G-rich nucleic acid sequences. These structures harbor significant biological importance as they are involved in telomere maintenance, transcription, and translation. Owing to their dynamic and polymorphic nature, G4 structures relevant for therapeutic applications need to be stabilized by small-molecule ligands. Some of these ligands turn on fluorescence upon binding to G4 structures, which provides a powerful detection platform for G4 structures. Herein, we report the synthesis of fluorescent ligands based on the indolyl-quinolinium moiety to specifically stabilize G4 structures and sense DNA. CD titration and melting experiments have shown that the lead ligand induces the formation of parallel G4 with preferential stabilization of the c-MYC and c-KIT1 promoter G4s over the telomeric, h-RAS1 G4, and duplex DNA. Fluorimetric titration data revealed fluorescence enhancement when these ligands interact with G4 DNA structures. The fluorescence lifetime experiment of the ligand with different DNAs revealed three excited state lifetimes (ns), which indicates more than one binding site. MD studies showed that the ligand exhibits 3 : 1 stoichiometry of binding with c-MYC G4 DNA and revealed the unique structural features, which impart selectivity toward parallel topology. The ligand was found to have low cytotoxicity and exhibited preferential staining of DNA over RNA. Collectively, the results presented here offer avenues to harness indolyl-quinolinium scaffolds for sensing and selective stabilization of G4 structures.